Part – I: Development of a Two-step Regiospecific Synthetic Route for Multigram Scale Synthesis of Β-carboline Analogs for Studies in Primates as Anti-alcohol Agents,part – II: Design and Synthesis of Novel Antimicrobials for the Treatment of Drug Resistant Bacterial Infections Part – Iii: A Novel Synthetic Method for the Synthesis of the Key Quinine Metabolite (3S)-3-Hydroxyquinine - (:unkn) unknown (My University, 2017)
PART – I Development of a Two-Step Regiospecifc Synthetic Route for Multigram-Scale Synthesis of β-Carboline Analogs for Studies in Primates as Anti-Alcohol Agents β-Carboline and their derivatives are important structural motifs in synthetic organic and medicinal chemistry because of their novel biological activity, especially in regard to the reduction of alcohol self-administration [binge drinking (BD)], a major problem increasing day by day in modern society. This anti-alcohol effect is proposed to be due to the activity of ligands at the benzodiazepine site of the GABAA receptor in the central nervous system acting as antagonists at the α1 subunit. The past evidence by June, Gondre-Lewis, and Weerts et al. of the biological importance of β-carbolines for the treatment of alcohol abuse has prompted the design and synthesis of a new series of analogs to improve the in vitro and in vivo pharmacological properties. Initial SAR studies on these β-carbolines revealed that βCCt (3) and the more water soluble analog, 3-PBC·HCl (1·HCl) were lead ligands for they had been shown to reduce alcohol self-administration in alcohol preferring (P) and high alcohol drinking (HAD) rats by June et al. with little or no effect on sucrose self-administration and no anhedonia nor depression. With this important activity, further studies were designed in higher animal models such as non-human primates (Weerts). However, the availability of these ligands for biological studies was the limiting step because of the long synthetic route and overall low yields. Consequently, a novel short two-step palladium catalyzed protocol was developed which consisted of a combined regioselective Buchwald-Hartwig amination and an intramolecular Heck-type cyclization to gain regiospecific access to 3,6-disubstituted β-carbolines. This regiospecific two-step synthetic protocol reduced the number of steps from 6 to 2 and permitted execution in excellent yields on a large scale (50 - 80 grams). To obtain ligands with anti-alcohol effects that were more water soluble than the active anti-alcohol compound βCCt (3) by using 3-PBC·HCl (1·HCl) as the guide, 3-ISOPBC·HCl (2·HCl) was synthesized which showed more potent activity in the reduction of alcohol self-administration than 1·HCl in a maternally deprived (MD) rat model for binge drinking. Later pre-clinical studies were conducted in non-human primate models such as baboons which required 80-100 grams of 3-ISOPBC·HCl. This can now be accomplished with ease using the new Pd chemistry. The pronounced activity of 2·HCl in non-human primates does imply it is a potential ligand to treat human alcoholics without the side effects of diazepam (one of the drugs employed now). These results led to the synthesis of 3-cycloPBC·HCl (20·HCl) which was active, to date, in MD rats without effecting the sucrose responding. The 3-cycloPBC·HCl was not cytotoxic at all when compared to βCCt, 3-PBC·HCl, 3-ISOPBC·HCl; the latter 3 ligands of which did exhibit some toxicity but only at very high concentrations. The microsomal stability studies on human and mouse liver microsomes of 20·HCl revealed it was longer lived in vitro than 3-PBC·HCl, and 3-ISOPBC·HCl. Further studies will need to be carried out in primate models to see if 20·HCl is a potential novel therapeutic agent to combat alcohol drinking and substance use disorders. PART – II Design and Synthesis of Novel Antimicrobials for the Treatment of Drug Resistant Bacterial Infections The alarming increase in bacterial resistance over the last decade along with a dramatic decrease in new treatments for infections has led to problems in the healthcare industry. A world-wide threat with HIV co-infected with multi and extensively drug-resistant strains of tuberculosis (TB) and methicillin-resistant Staphylococcus aureus (MRSA) has emerged and is responsible for several million deaths per year. In this regard, herein, novel acrylic acid ethyl ester derivatives were synthesized in simple, efficient routes, and evaluated as potential agents against a panel of gram positive, negative, mycobacterial, and clinically significant resistant strains including M. tuberculosis (Mtb) for minimum inhibitory concentrations (MIC). In depth structure activity relationship (SAR) studies of acrylic acid ethyl ester derivatives revealed that the ethyl esters 59 and 63 were found to be very potent (MIC = 0.72 and 0.69 µg/mL) against actively replicating Mtb. Importantly, scaffolds 59 and 63 exhibited six and four fold greater inhibition, respectively, against nonreplicating persistent (dormant) phenotypes under low oxygen conditions than isoniazid; this is essential to decrease the duration of tuberculosis treatment from many months to less time. Further evaluation of these selected analogs 59 and 63 against a panel of single-drug resistant Mtb strains indicated a similar level of activity as against wild type Mtb. This encouraging safety profile is key with a selective index greater than 10. Gratifyingly, the ethyl ester 59 retained excellent inhibition with MIC values of 0.25-4.0 µg/mL against a wide variety of virulent antibiotic-resistant clinical isolates (MRSA, MDR MRSA, VISA MRSA, and VRE). This exciting activity provided a path to determine the molecular target for this novel class of compounds with the copper catalyzed azide-alkyne 1,3-dipolar cycloaddition (CuAAC) Click reaction because of the availability of alkyne functionality in 59. By treating Staphylococcus aureus lysates with Alexa fluor 647 picolyl azide (AF647), one identified S. aureus proteins that had been covalently modified by propargyl ligand 59. SDS-PAGE analysis of the fluorescently labeled proteins showed that only two proteins were labeled. Encouraged by the results, AF647 was replaced with biotin azide to isolate the target proteins using streptavidin beads. Later, the purified protein fractions were subjected to peptide mass fingerprinting for protein identification. Data analysis of these samples using MaxQuant 1.4.1.2 against the Uniport database for E. coli and S. aureus identified three enzymes as potential targets: enolase (Uniprot ID: P64079), dihydrolipoyllysine-residue acetyltransferase (Uniprot ID: Q8NX76), and glyceraldehyde-3-phosphate dehydrogenase (Uniprot ID: P0A037). These enzymes are well-known to be involved in glycolysis and act as virulence factors responsible for the pathogenicity of S. aureus. Thus far, attempts to validate the structure of S. aureus enolase by X-ray diffraction analysis have been unsuccessful, since one has been unable to obtain diffraction-quality crystals of this protein; however, protein docking experiments with S. aureus enolase have been successful. Further work on these potent antimicrobial agents would benefit from the knowledge of the binding site as well as interactions between the ligand and the proteins; the mode of inhibition. The identification of the bimolecular interaction between the ligand 59 and target proteins would potentially result in new drugs to treat drug resistant infections from bacteria, including MRSA, MDR VISA, and VRE. The investigation of ADMET medicinal chemistry properties of select agents including 59 and 63 is ongoing in our laboratories. Part – III A Novel Synthetic Method for the Synthesis of the Key Quinine Metabolite (3S)-3-Hydroxyquinine The Cinchona alkaloid quinine (1) remains unique among the thousands of natural products isolated and characterized to date because it still remains the drug of choice for the treatment of severe and complicated malaria in most parts of the world. Apart from biological activity, Cinchona alkaloids play a vital role in organic chemistry from racemate resolutions to promote enantioselective transformations in both homogeneous and heterogeneous catalysis. The synthesis of the major metabolite of quinine (1), 3(S)-3-hydroxyquinine (7) has been accomplished by a shorter route, devoid of the previously employed toxic reagent (HBr gas) and separated from its epimeric mixture [4(S):1(R)] at C-3 by conversion into the 9-aceto analogue followed by flash column chromatography. The molecular structure of the major acetate diastereomer 9 was further confirmed by X-ray crystallographic analysis, and this unambiguously confirms the absolute configuration of 3(S)-3-hydroxyquinine (7). The new synthetic protocol increased the overall yield from 16% to 53% and makes essential metabolite 7 more readily available now for scientists and doctors to study drug-drug interactions when using quinine with another agent to treat, malaria combined with HIV (ritonavir) or other comorbid situations. For instance, a doctor in Nigeria, using 7 found that in healthy volunteers, to treat patients with HIV and malaria one needed a ratio of ~5:1 ritonavir and quinine, not 1:1, as used previously.
Keywords: 3(s)-3-hydroxyquinine; Anti-alcohol Agents; Drug Resistant Bacterial Strains; MRSA; TB; Novel Acrylic Acid Ethyl Ester Derivatives; Β-carboline